أثر الإبداع التنظيمي في علاقة التمكين الإداري بالأداء الوظيفي للعاملين - رحال, الزهرة; سعد الله, كريمة; جبالي, سارة (University of eloued جامعة الوادي, 2019)
تهدف هذه الدراسة إلى معرفة كيفية مساهمة الابداع التنظيمي في العلاقة بين التمكين الإداري والأداء الوظيفي للعاملين . ونصت فرضية هذه الدراسة على وجود وساطة كلية للإبداع التنظيمي في العلاقة بين التمكين الإداري والأداء الوظيفي للعاملين بمؤسسة توزيع الكهرباء والغاز بالوادي. إذا اعتمدت الدراسة على الاستبيان كأداة لجمع البيانات من عينة الدراسة البالغة 60 عاملا بالمؤسسة. كما اتبع أسلوب المنهج الوصفي الاستدلالي لتحليل البيانات والتي تم الحصول عليها وتحليلها من خلال استخدام برنامج SPSSV25وبرنامج AMOSV24 . حيث استخدمت جملة من الأدوات الإحصائية كالتكرارات والنسبة المئوية والمتوسط الحسابي والانحراف المعياري والأهمية النسبية وتحليل الانحدار البسيط وتحليل المسار في تحليل الفرضيات . وخلصت الدراسة إلى جملة من النتائج وهي وجود تأثير(مباشر) بين التمكين الإداري والإبداع التنظيمي في مؤسسة توزيع الكهرباء والغاز بالوادي ووجود تأثير(مباشر)بين الابداع التنظيمي والأداء الوظيفي للعاملين في المؤسسة . و وجود تأثير(مباشر وغير مباشر) بين التمكين الإداري والأداء الوظيفي للعاملين. ومنه وجود وساطة جزئية للإبداع التنظيمي في علاقة التمكين الإداري للأداء الوظيفي للعاملين في مؤسسة توزيع الكهرباء والغاز بالوادي. The aim of this study is to know how organizational creativity contributes to the relationship between administrative empowerment and job performance. The hypothesis of this study is that there is a total mediation of organizational innovation in the relationship between administrative empowerment and job performance of the employees of the Electricity and Gas Distribution Corporation in EL-Oued. If the study relied on the questionnaire as a tool for collecting data from the study sample of 60 employees in the institution. The method of descriptive descriptive approach to data analysis, obtained and analyzed through the use of SPSSV25 and AMOSV24. A number of statistical tools were used, such as frequency, percentage, arithmetic mean, standard deviation, relative importance, simple regression analysis, and path analysis in hypothesis analysis. The study concluded that there is a direct influence between administrative empowerment and organizational creativity in the institution of electricity and gas distribution in EL-Oued and the presence of direct influence between the organizational creativity and the performance of the employees of the institution. And a direct and indirect impact between administrative empowerment and employee performance. And there is partial mediation of organizational innovation in the relationship of administrative empowerment of the performance of employees in the Electricity and Gas Distribution Corporation in EL-Oued.
مذكرة ماستر تخصص ادارة أعمال
Keywords: تمكين إداري، ابداع التنظيمي، أداء العاملين.; : Empowerment, organizational creativity, employee performance